Предмет: Алгебра,
автор: nctuline
решить уравнение. объясните, пожалуйста, подробно!
Приложения:
Ответы
Автор ответа:
1
((x+6)^2-(6-x)^2)/(36-x^2)=(x^2+12x+36-36+12x-x^2)/(36-x^2)=24x/(36-x^2)
24x/(36-x^2)-6/(36-x^2)=0
24x-6=0
24x=6
x=0,25
24x/(36-x^2)-6/(36-x^2)=0
24x-6=0
24x=6
x=0,25
nctuline:
спасибо огромное <33
Похожие вопросы
Предмет: Русский язык,
автор: krgpslagakurilkf
Предмет: Английский язык,
автор: kkhgfdrthfrtyigcdfth
Предмет: Геометрия,
автор: nepon4799
Предмет: Математика,
автор: MÄG2612
Предмет: Математика,
автор: yanaolok